Translation Methods Found in New Testament Bible of Mark’s Gospel - Ni Wayan Swarniti (RETORIKA: Jurnal Ilmu Bahasa, 2021)
Language is one of the important things in human life. By using the language, we can communicate with others. This research tried to analyze the bible translation by using methods of translation theory by Newmark (1988). This research was a qualitative research that focused to analyze the Gospel according to Mark. Bible entitled New Testament (2005) was published by The Indonesian Bible Society for The Gideons International. It was printed by Percetakan Lembaga Alkitab Indonesia. The book consists of 727 pages. Informal method was used to present the results of the analysis. It was the explanation of the translation methods used. Formal method was used to describe the table of the frequency of the translation methods applied in the bible translation found in new testament bible of Mark’s gospel. The translation methods found in data source were word for word translation, literal translation, faithful translation, semantic translation, free translation, idiomatic translation, and communicative translation. Adaptation was not found in all chapters of data source. The most translation method applied in new testament bible of Mark’s gospel was free translation. Free translation had the highest percentage in every chapter in new testament bible of Mark’s gospel. In the other word, the translator tried to transfer the meaning from source text into target text with changing the form based on cultures in target language.